The optimal use of exhaustible resources under non-constant returns to scale - Sergey Aseev; Konstantin Besov; Serguei Kaniovski (Austrian Institute of Economic Research (WIFO), 2016)
The paper offers a complete analysis of the welfare-maximising capital investment and resource depletion policies in the Dasgupta-Heal-Solow-Stiglitz (DHSS) model with capital depreciation and any returns to scale. We establish a general existence result and show that an optimal admissible policy may not exist if the output elasticity of the resource equals 1. We characterise the optimal policies by applying an appropriate version of the Pontryagin maximum principle for infinite-horizon optimal control problems. We conclude the paper with an economic interpretation and a discussion of the welfare-maximising policies.
Keywords: C61; O38; Q01; Q56; 330; optimal growth; nonconstant returns to scale; exhaustible resources